PSI-30 Identifying key regulator genes associated with parasite resistance and their link with climate conditions in sheep. (7th December 2018) - Dixon, S; Karrow, N; Cánovas, A; Borkowski, E; Menzies, P; Boareki, M; Fonseca, P; Suárez-Vega, A; Kennedy, D; Peregrine, A; Mallard, B
Abstract: Gastrointestinal nematode (GIN) infections are a common cause of morbidity and mortality in grazing sheep. Among these GINs, one of the most pathogenic is Haemonchus contortus . Control of this parasite relies heavily on anthelmintics, but alternatives must be explored because H. contortus can rapidly develop anthelmintic resistance. Climate change will not only affect the sheep's ability to fight GIN infection, but also influence the life cycle, parasite load, and pasture contamination of H. contortus . All of these factors highlight the importance of developing alternative tools, such as genetic selection for resistance to H. contortus infection, which can be used as part of a sustainable integrated parasite-management program. Abomasum tissues, the primary target tissue of H. contortus, were collected from previously phenotyped HIGH and MIDDLE stress responding sheep (n=29) and control sheep (n=8), to examine the abomasum transcriptomic profile associated with the parasite burden. Principle Component Analysis was performed using HIGH (n=14) and MIDDLE (n=15) stress responding sheep using R. The included components were: fecal egg count, cortisol level, CarLA saliva test, red blood cell count, hematocrit and abomasum worm count. Additionally, t-test analysis was performed to confirm significant differences between these two groups (HIGH and MIDDLE). Among these sheep, eight were selected to perform RNA-Sequencing analysis from; HIGH stress responders (n=4) and MIDDLE stress responders (n=4) with a significant difference between these groups of animals (p=0.086). RNA isolation was performed from these selected animals (n=8) in addition to control animals (n=4). Differential gene expression analysis between HIGH and MIDDLE stress responding sheep and identification of structural variants associated with the stress response will be performed using RNA-Sequencing. In addition, climate data will be collected over two grazing seasons, to examine a correlation between climate conditions and H. contortus pasture contamination and host load.